«Nurly zhol»: тhe direction of the efficient infrastructure - Otepbergen, K. E. (Journal of Economic Research & Business Administration, 2016)
This article describes the development of infrastructure under the program approved by the state policy«Nurly Zhol» 2015-2019. The main aspect of this policy is the integration of micro-regions in the country and the formation of a common market based on the new growth. Within the framework of short-term and long-term growth of the program ensured the preservation of jobs and creation of new jobs, increased business activity and performance of the regions is expected to increase the country’s transit potential. Full implementation of the program«Nurly Zhol» is calculated until 2020.«Nurly Zhol» program consists of two parts. The first block of the country’s infrastructure development, the project will be implemented in 7 areas. This article describes the primary outcome in all 7 areas. In 2015, the«Nurly Zhol» provides a comprehensive plan for the second block of anti-crisis measures. Within the framework of the goals and objectives of the program were analyzed main indicators and the results of implementation of indicators.